Reconfiguring Outward-Oriented Internationalization Management in Higher Education: Institutional Logics and Stakeholder Dynamics - Guijun Zhang; Muhammad Faizal (Universitas Pendidikan Ganesha, 2025)
Despite national-level efforts to enhance China’s higher education global standing, limited research has examined how outward-oriented internationalization is interpreted and enacted at the institutional level. Misalignments often persist between policy directives and localized implementation in semi-peripheral context.This study aims to critically examine the institutional factors and stakeholder dynamics that shape the management of outward-oriented internationalization in Chinese higher education. Drawing on a qualitative multiple-case study approach, the research synthesizes insights from 12 semi-structured interviews, observational data, and institutional documents across three diverse universities. Thematic analysis using NVivo software identified three major findings: (1) varied institutional translations of centralized mandates, (2) performance-driven internationalization logics influenced by incentive structures, and (3) intercultural tensions reflected in the lived experiences of faculty and international students. The findings reveal systemic tensions between global competitiveness goals and local cultural practices, underscoring the limits of top-down strategies. This study contributes theoretically by integrating world-systems, soft power, and Confucian institutionalism, and practically by offering actionable strategies to enhance sustainable and inclusive internationalization in higher education.